Depending on Practice: Paul Ricoeur and the Ethics of Care - Carney, Eoin (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Continuing on from recent discussions on the overlap between Paul Ricoeur’s philosophy and care ethics, this article will aim to clarify the status of practice in Ricoeur’s work. I will argue that even though Ricoeur’s philosophy is indeed marked by its “desire for a foundation,” as care ethicist Joan Tronto has pointed out, this aim is more of a fragile wager than a principle, and is always at risk of being overturned by practices and other worldviews. I will demonstrate this point by arguing that (1) Ricoeur’s hermeneutic approach to practice leads to the view that objective methods of knowledge and explanation are always grounded by the broader hermeneutic task of practical understanding and care for the self; (2) in moral reasoning, Ricoeur’s analysis of the conflict between respect for the rule and respect for persons results in his prioritizing of respect for the singular other rather than the universal rule, meaning that the other can always disrupt and reorient universal or foundational modes of reasoning; and finally (3) within healthcare relations Ricoeur aims to develop an alternative understanding of respect that places it in a dialectical relation with care. These practice-oriented readings of hermeneutics, morality, and respect aim to open up a dialogue between care ethics and philosophical approaches that have often been placed outside of care ethics.